(3GdeYjfs - (3MHjH Gddg Hf bGVjs ((3ehQjJGfjG s)
(3ChdgG (B:s
(3HGH ai GdHjY hgh HGH jfHZi GdGYJfGA Hg dcKQI bhGYOg hJTYH aQhYg GdMGLI Edjg s
(3BNQgG (B:s
(3Ch fHV dg KOi Ohf dMjI Ch MUd ef MjV Ohf Ch MUd efi Ohf MjV adG CTcGd ajg hGddg JYGdi CYde HLjeY GdcJGH hgh GTed hCLed GfJgi hJe HMeO Gddg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3WeSJ HYV cdeGJgGs
(3HBNQgG Jedc s
(3hgj ecJhHI HGdMHQ GdCShO hGdCMeQ s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdESdGejs